The Effect Of Company Performance On Stock Return In The Consumption Goods Sector - Vinny Larasati; Hesty Juni Tambuati Subing; Amin Mansur (Journal of Accounting, Management, and Economics Research (JAMER), 2023)
The purpose of this study is to determine the effect of company performance on stock returns in the consumer goods sector for the period (2016-2020) and its review from an Islamic point of view. Company performance as proxied by variables ROA, CR, DER, TATO and PER. The research method used is quantitative research methods and uses secondary data. The sample used as many as 16 companies through purposive sampling method. The analytical method used is panel data regression analysis technique with a significant level of 5%. The results of this study indicate that: (1) Return on Assets (ROA) has a significant effect on stock returns (2) Current Ratio (CR) has no significant effect on stock returns (3) Debt To Equity Ratio (DER) has no significant effect on return stocks (4) Total Assets Turnover (TATO) has a significant effect on stock returns (5) Price Earnings Ratio (PER) has a significant effect on stock returns (6) ROA, CR, DER, TATO and PER simultaneously have a significant effect on stock returns.